Learning Model AIK 1 (Aqidah) in College Based on Educations Velue: Model Pembelajaran AIK I (Aqidah) Di Perguruan Tinggi Berbasis Pendidikan Nilai - Nisa', Miratun (Universitas Muhammadiyah Sidoarjo, 2020)
The challenges of al-Islam and Muhammadiyah Education or abbreviated as AIK include the curriculum that is not yet fully in line with Muhammadiyah's vision and mission, not yet balanced between affective cognitive and personality, unstructured material and struc- tured learning material that is dense but does not have a spirit or meaning. Various studies have been conducted an effort to advance AIK education which is more striking but AIK related research is still theoritical and methodological approach .So that this article gives the colors of AIK learning models based on educational values. Based on these objec- tives, this article uses the literature literary method with sources that support the AIK curriculum in the AIK Education Guidelines for the Muhammadiyah Council of DikTi PP. The result of this article is education syllabi of AIK that more practical and implemen- tative. Through this assessment, the lecturer can instill beneficial values in students in accordance with increasing faith and Islamic values as an increase of applicable learning.